THE BASIC PRINCIPLES OF LEGAL GOVERNANCE OF PRIVATE BANKS IN THE REPUBLIC OF UZBEKISTAN - R.Arziboyeva (Scholar Express Journals, 2023)
The article examines the methodology and aspects of regulating private bank operations in the Republic of Uzbekistan, as well as the steady development of the regulatory framework and practical issues in the field of banking regulation
Keywords: Bank; Banking Regulations; Banking System